Evaluation Of Sediment Transport Equation In Southeast Asia - Isa, Nurfazlina (Universiti Sains Malaysia, 2022)
The continent of Southeast Asia was chosen for the study area because Malaysia is one of the countries on the continent. The country in Southeast Asia has a hot, humid, tropical climate with monsoons and heavy precipitation. Subsequently, this continent was chosen due to its tropical climate, which will influence the characteristics of the rivers in its countries. Malaysia, Indonesia, Singapore, Thailand, and Vietnam are the countries involved in this research. The remaining six countries on the continent are not involved, as the relevant research paper was only discovered in these five nations. More than 400 papers related to this paper were identified through a search of credible sources and subsequently screened. After the screening, 33 primary papers were discovered. The elimination of duplicate papers and unrelated topics based on their titles and abstracts required the use of screening procedures. The papers were evaluated and analyzed, and the results were presented in Microsoft Excel tables. Graphs and charts were also used to illustrate the results. The principal focus of this study is the sediment transport equation utilized in Southeast Asian countries. This study discusses the sediment transport equation from previous studies that have been frequently used and mentioned.